Patterns and motivations for method choices in suicidal thoughts and behaviour: qualitative content analysis of a large online survey - Lisa Marzano; Dafni Katsampa; Jay-Marie Mackenzie; Ian Kruger; Nazli El-Gharbawi; Denika Ffolkes-St-Helene; Hafswa Mohiddin; Bob Fields (BJPsych Open, 2021)
Background Choice of suicide method can strongly influence the outcome of suicidal behaviour, and is an important aspect of the process and planning involved in a suicide attempt. Yet, the reasons why individuals consider, choose or discard particular methods are not well understood.